2014
DOI: 10.1111/j.1532-950x.2014.12273.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screw Type and Distribution on the Torsional Stability of 3.5 mm String of Pearls Locking Plate Constructs

Abstract: A minimum of 1 bicortical screw/fragment should be used to increase torsional stability of 3.5 mm SOP constructs. Positioning this screw at the inner- or outermost positions relative to the fracture is preferred, with the innermost position providing the greatest improvement in stability. Should further torsional stability be desired, increasing the number of bicortical screws is recommended. Clinically, these results may assist with preoperative planning of various fracture patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Monocortical screws have been found mechanically acceptable in a bone model using locking plates, if combined with at least one bicortical screw in each fracture segment. The bicortical screws would ideally be placed close the fracture line, with the distant placement considered the second best configuration for torsional stiffness . Our results show that bicortical screw placement close to a diaphyseal fracture site is not feasible in plate‐rod constructs in feline tibiae due to the narrow medullary canal in the mid‐diaphysis, and likely interference with the IM pin.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Monocortical screws have been found mechanically acceptable in a bone model using locking plates, if combined with at least one bicortical screw in each fracture segment. The bicortical screws would ideally be placed close the fracture line, with the distant placement considered the second best configuration for torsional stiffness . Our results show that bicortical screw placement close to a diaphyseal fracture site is not feasible in plate‐rod constructs in feline tibiae due to the narrow medullary canal in the mid‐diaphysis, and likely interference with the IM pin.…”
Section: Discussionmentioning
confidence: 91%
“…Another limitation of our study is that we did not evaluate bicortical locking screws. We chose to test M‐lock because previous studies have suggested that a plate‐rod construct with M‐Lock may provide sufficient stability for clinical use, especially including B‐cort screws in the metaphyseal area . Being an ex vivo study, the results of the cadaveric simulation may also be limited by the reduced elasticity of cadaveric bones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocortical screws may be utilized if the intra-medullary pin is contacted during screw insertion, although at least one bicortical screw should optimally be placed in each bone fragment to optimize torsional stability. 39 The bicortical screws would ideally be placed close the fracture line, with the distant placement considered the second best configuration for torsional stiffness. 36 There are several limitations to this study, mainly stemming from the retrospective design.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, a single bicortical screw in the proximal segment may also decrease resistance to torsion. 33 Contemporary low profile anatomically contoured locking compression TPLO plates with proximal screws angulating away from the articular surface have shown higher median osteotomy union scores and marginally lower complications rates. 7,9,10,25 A future study of osteotomy union comparing compression to non-compression TPLO procedures is warranted.…”
Section: Discussionmentioning
confidence: 99%